2021
DOI: 10.3389/fspor.2021.714555
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in Reactive Balance Strategies in Healthy Older Adults After a 3-Week Perturbation Training Program and After a 12-Week Resistance Training Program

Abstract: Both resistance training (RT) and perturbation-based training (PBT) have been proposed and applied as interventions to improve reactive balance performance in older adults. PBT is a promising approach but the adaptations in underlying balance-correcting mechanisms through which PBT improves reactive balance performance are not well-understood. Besides it is unclear whether PBT induces adaptations that generalize to movement tasks that were not part of the training and whether those potential improvements would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
(144 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, our results demonstrate limited transfer of different reactive paradigms. These findings are in accordance with previous studies that showed that reactive balance tasks were not necessarily improved if they differed from the trained paradigm [13, 43].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our results demonstrate limited transfer of different reactive paradigms. These findings are in accordance with previous studies that showed that reactive balance tasks were not necessarily improved if they differed from the trained paradigm [13, 43].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, exercising walking might also improve leg strength [48]. However, some other PBT studies did not find effects on muscle strength in healthy older adults [12, 18, 36, 43], but these either included only static perturbation training or only a small amount of training sessions. The descriptive leg strength improvements in PBT stability of 5% lay in between the results of previous studies investigating the same training paradigm in healthy older adults that found improvements of 3–11% in knee extension strength capacity [14, 16].…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning for ongoing translation, given that a population-level association does not necessarily equate with prediction at an individual level ( 15 17 ). Although successful balance strategies that involve proactive or reactive adaptations are directly involved in avoiding a fall ( 18 20 ), there is insufficient investigation as to whether poor one-legged balance performance predicts subsequent falls and what constitutes the threshold for a positive screening result ( 7 ).…”
Section: Introductionmentioning
confidence: 99%